2002
DOI: 10.1051/0004-6361:20020549
|View full text |Cite
|
Sign up to set email alerts
|

Abundance analysis of targets for the COROT/MONS asteroseismology missions

Abstract: Abstract.One of the goals of the ground-based support program for the COROT and MONS/Rømer satellite missions is to select and characterise suitable target stars for the part of the missions dedicated to asteroseismology. While the global atmospheric parameters may be determined with good accuracy from the Strömgren indices, careful abundance analysis must be made for the proposed main targets. This is a time consuming process considering the long list of primary and secondary targets. We have therefore develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 20 publications
7
61
0
Order By: Relevance
“…We found v sin i = 70 km s −1 using Hα and v sin i = 80 km s −1 using H β . This is in good agreement with the value of v sin i = 84 km s −1 measured by Bruntt et al (2002).…”
Section: Rotation Of Other Starssupporting
confidence: 91%
“…We found v sin i = 70 km s −1 using Hα and v sin i = 80 km s −1 using H β . This is in good agreement with the value of v sin i = 84 km s −1 measured by Bruntt et al (2002).…”
Section: Rotation Of Other Starssupporting
confidence: 91%
“…The method is the same as employed by Dall et al (2005), adopted from the procedures of Morel et al (2003) and Bruntt et al (2002Bruntt et al ( , 2004. The first step is the measurement of the EWs, which is accomplished using DAOSPEC 1 (Stetson & Pancino 2005, in preparation), which uses an iterative Gaussian fitting and subtraction procedure to fit the lines and the effective continuum.…”
Section: Abundance Analysis: Methodsmentioning
confidence: 99%
“…The software is called VWA which has a graphical user interface (GUI). The method and the VWA software have been described in detail by Bruntt et al (2002Bruntt et al ( , 2004 and the method compared to the classical EW method by Bikmaev et al (2002). The abundance analysis relies on atomic parameters from the VALD database (Kupka et al 1999;Piskunov et al 1995) and uses modified ATLAS9 atmospheric models from interpolation in the grid published by Heiter et al (2002).…”
Section: Abundance Analysis: Methodsmentioning
confidence: 99%
“…Strömgren photometry, taken in 2001, confirmed the variability with excess power in the 1 d −1 to 5 d −1 region, but yielded no identifiable frequencies (Bruntt et al 2002). Further spectroscopy by Mathias et al (2004) showed, again, low-amplitude variations in the blue wing of the line profile.…”
Section: Introductionmentioning
confidence: 89%
“…The spectroscopic parameters from these works and those from two further photometric studies by Lastennet et al (2001) and Poretti et al (2005) are given in Table 1. The radius of the star is estimated from 2mass infra-red photometry to be 1.601 ± 0.052 R⊙ (Masana et al 2006) and an estimate of the stellar mass of 1.55 ± 0.14 M⊙ is given in Bruntt et al (2002).…”
Section: Introductionmentioning
confidence: 99%